Teachers' perspectives on factors affecting the inclusion of ADHD students in Greek mainstream classrooms - Lilikaki, Styliani (2015)
Within a huge debate regarding the issue of Attention Deficit Hyperactivity Disorder (ADHD), teachers are the ones responsible to promote the inclusion of ADHD students which is supported by the latest Greek law. However, their perspectives and experiences have never been asked so far. This study aims to explore Greek teachers’ perspectives (N=7) considering the factors that affect the inclusion of ADHD students through semi-structured interviews. Regarding students with ADHD the term inclusion does not refer only to relocation. It acquires a broader meaning of equal participation in every aspect of school life with their classmates and experiencing the best possible quality of education. By revealing factors that hinder the students’ inclusion, solutions can be found while factors who led to successful inclusion can be promoted. Analysis demonstrated that according to teachers, their lack of knowledge and emotions of frustration, students’ ADHD-related behaviours and their aftereffects, lack of human support, equipment and limited time for creative activities are factors that can negatively affect the inclusion of students. Conversely, teachers’ positive attitudes towards students with ADHD, effective teaching strategies with a focus on the creation of caring relationships and the promotion of ADHD students’ talents were factors resulting in successful inclusion. Finally, implications for practise according to the findings are discussed.